Alinhavando algumas ideias sobre formação e cultura: o Brasil em tempos de regressão - Kropf, Paula (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The purpose of this article is to present ideas for the development of the doctorate thesis. That aims to observe sense of the culture considering the social formation in progress and current landmarks. From the essay "Os sete fôlegos de um livro", by Roberto Schwarz, to rescue ideas related to the brazilian formation process, and examine them in the light of Brazil enrolled in globalized capitalism. Unlike the early twentieth century authors pointed out, concerned with understanding the process of organization of brazilian social life, the formation of the country was not to come, along with modernity. Instead, there was already completed and underdevelopment was our way. In this context, what are the possibilities of culture as a unit, subordinate to current economic relations, whose rule is the dissociation?
Keywords: social formation; culture; Schwarz; capitalism